Figurabile - Bonito Oliva, Achille; Studio Ghiglione, Genova (Genova : Studio Ghiglione, 1988)
Schifano, Mario ; Boero, Renata ; Ceccobelli, Bruno ; Gallo, Giuseppe ; Cannella, Pizzi ; Ragalzi, Sergio ; Tirelli, Marco
Figurabile, Studio Ghiglione, Genova, giugno - luglio 1988
boek